Penghambatan Kekerutan Pada Kulit Tomat Dengan Edible Coating Limbah Ampas Tebu dan Gathot (Singkong Terfermentasi) - Ratnaduhita, Astari; Kholis, Muhammad Nur; Sumirat, Riska (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Tomatoes have thin peels that are susceptible to post-harvest damage, especially in tropical climates such as Indonesia. An effort to prevent damage is cold storage. However, cold storage causes chilling injury to tomato peel. This study aims to develop an edible coating formulation with bagasse and gathot (fermented cassava), and to determine the best treatment of the edible coating by application to tomato at cold storage for 21 days. The research was designed using a completely randomized design (CRD) with a gathot flour concentration of 0.75% and a variation of sugarcane bagasse flour concentration, namely: 0%; 1%; 2%; 3%. The parameters observed were weight loss, pH, total soluble solids and moisture content and analyzed by parametric statistics with a significance level of 5%. The results showed that the edible coating formulation with sugarcane bagasse flour and gathot flour had a significant effect (α < 0.01) on changes in weight loss, total soluble solids, pH and moisture content in tomatoes for 21 days. Edible coating with C1 formulation (sugarcane bagasse flour 1% and gathot flour 0,75%) became the best treatment of this study because it was able to maintain freshness and showed inhibition of chilling injury in tomatoes until day 21 in cold storage.